Dynamic regulatory interaction between cytomegalovirus major tegument protein pp65 and protein kinase pUL97 in intracellular compartments, dense bodies and virions - König, Patrick; Buescher, Nicoie; Steingruber, Mirjam; Socher, Eileen; Sticht, Heinrich; Tenzer, Stefan; Plachter, Bodo; Marschall, Manfred (Journal of General Virology, 2017)
Human cytomegalovirus (HCMV) is a ubiquitous pathogen of considerable clinical importance. Understanding the processes that are important for viral replication is essential for the development of therapeutic strategies against HCMV infection. The HCMV-encoded protein kinase pUL97 is an important multifunctional regulator of viral replication. Several viral and cellular proteins are phosphorylated by pUL97. The phosphoprotein pp65 is one important substrate of pUL97. It is the most abundant tegument protein of HCMV virions, mediating the upload of other virion constituents and contributing to particle integrity. Further to that, it interferes with host innate immune defences, thereby enabling efficient viral replication. By applying different approaches, we characterized the pp65-pUL97 interaction in various compartments. Specifically, the pUL97 interaction domain of pp65 was defined (282-415). A putative cyclin bridge that enhances pUL97-pp65 interaction was identified. The impact of pUL97 mutation on virion and dense body morphogenesis was addressed using pUL97 mutant viruses. Alterations in the proteome of viral particles were seen, especially with mutant viruses expressing cytoplasmic variants of pUL97. On the basis of these data we postulate a so far poorly recognized functional relationship between pp65 and pUL97, and present a refined model of pp65-pUL97 interaction.
EVALuna2:33718